Pentingnya Menjaga Etika dalam Berbisnis pada Desa Tomok Parsaoran Nauli, Kec. Simanindo, Kab – Samosir - Lbn. Raja, Edward Alezandro; Lbn. Raja, Togu Harlen (Jurnal Mitra Pengabdian Farmasi, 2022)
Ethics is very necessary in business activities, so that business can run well and can be maintained by business people in the future. Business ethics is closely related to the morality of business people so that there are business norms that must be agreed upon by business people so that every business person will be subject to the moral values ​​that exist in business life. With the existence of ethics, a harmonious, harmonious and mutually beneficial business commitment is created between human groups as individuals or groups or institutions where the ethical reference in human life always refers to norms, social morality, statutory regulations or applicable laws that must be accepted by the community. everyone as a standard of human behavior. The number of traders who attended this service activity amounted to 56 people consisting of traders who were active in the Tomok Village Market Parsaoaran Nauli, Kec. Simanindo, Samosir Regency. From the evaluation of the results of this lecturer service activity, it can be explained that the traders who did not understand the socialization were 4 people or 7%, the traders who did not understand the socialization were 6 people or 10.7%, the traders who understood the socialization were 20 people or 35, 7 % and traders who really understand the socialization are 26 people or 46, 4%.